2010
DOI: 10.1007/s00127-010-0310-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and deliberate self-harm in Oxford University students over a 30-year period

Abstract: Contrary to earlier findings and popular belief, suicide rates in Oxford University students do not differ from those in other young people. Rates of DSH are significantly lower than in other young people. Risk of DSH may increase around the time of examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…Suicide attempts are also more common among 16 -24 year olds than older age groups (Nicholson et al, 2009). Previous studies have reported that the prevalence rates for suicide completion and attempts are similar or lower among students in higher education compared with age-matched general populations (Collins and Paykel, 2000;Hawton et al, 1995;Hawton et al 2012). This belies the suggestion that the stressors of university pose a greater threat for suicide.…”
Section: Discussionmentioning
confidence: 85%
“…Suicide attempts are also more common among 16 -24 year olds than older age groups (Nicholson et al, 2009). Previous studies have reported that the prevalence rates for suicide completion and attempts are similar or lower among students in higher education compared with age-matched general populations (Collins and Paykel, 2000;Hawton et al, 1995;Hawton et al 2012). This belies the suggestion that the stressors of university pose a greater threat for suicide.…”
Section: Discussionmentioning
confidence: 85%
“…The drugs used vary between different DSH populations but paracetamol, antidepressants and tranquilisers are among the most frequently used drugs. [25][26][27] There is a wide variation in the methods used all over the world owing to different access to suicide means, in the USA for example the use of firearms is more common and in Southeast Asia the use of pesticides. 28 29…”
Section: Womenmentioning
confidence: 99%
“…7,8 Third, with the recent increase in use of social media, information is lacking on the impact of exposure to suicide in social media on suicide contagion. Fourth, although there has been an increase in prevalence of nonsuicidal self-injury, 9 the longitudinal course and risk for death by suicide among people with non-suicidal selfinjury remains unknown. Fifth, most epidemiologic studies of suicidal ideation and attempts have been cross-sectional, may be affected by recall bias, and are not generalizable to death by suicide.…”
Section: Limitations Of the Current State Of Knowledge On Suicide Rismentioning
confidence: 97%